Serogroup detection, antibiotic resistance patterns and virulence gene profile of Escherichia coli isolated from diarrheic sheep - GAZAL, SABAHAT; TAKU, A K; BHAT, M A; KUMAR, BABLU; BADROO, G A (The Indian Journal of Animal Sciences, 2012)
Escherichia coli isolates (115) were obtained from faecal samples collected from diarrheic sheep in Jammu, J&K. All the isolates were subjected to virulence characterization by multiplex PCR using primers for stx1, stx2, eae and ehxA genes. A total of 19 (16.5%) isolates were found to harbour toxic genes, out of which 12 isolates carried stx1, 3 carried eae whereas 3 were detected positive for both stx1 and exhA genes. Only 1 of these 19 isolates was found to carry 3 genes (stx1, stx2 and eae). Upon serogrouping of all the isolates O69 was found to be the predominant serogroup (present in 30 of 115 isolates). In this study 12 serogroups were found. In vitro sensitivity test was also carried out to determine antibiotic resistance patterns of the isolates to various drugs. Maximum resistance was noted against antibiotics like polymixin and nitrofurantoin (38.46%) whereas maximum sensitivity was noted to chloramphenicol, ciprofloxacin and gentamicin (92%). Thus, these drugs can be recommended to treat diarrhoea in ovines.